2021
DOI: 10.1177/09645284211009544
|View full text |Cite
|
Sign up to set email alerts
|

Laser acupuncture versus oral glucose administration for pain prevention in term neonates: an observer-blinded non-inferiority randomized controlled clinical trial

Abstract: Background: Neonates undergoing intensive care are routinely submitted to minor painful procedures such as heel lances. Pharmacological treatment is limited in neonatal care and not recommended for minor painful interventions. Hence, non-pharmacological acute pain management is an important subject. Acupuncture could be a new strategy for neonatal pain prevention. Accordingly, the aim of the present study was to investigate whether laser acupuncture is non-inferior to oral sweet solutions in pain prevention. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(52 citation statements)
references
References 44 publications
(80 reference statements)
0
52
0
Order By: Relevance
“…Regarding the status of the neonates, 3 studies included healthy, full-term neonates 49,51,53 ; 1 study described sick, full-term neonates 55 ; 1 study involved sick, full-term neonates, and neonates in the mild preterm category (born 35 to 40+6 weeks of gestational age) 54 ; and 5 studies described preterm infants (born before 37 weeks of gestational age) 47,48,50,52,56 . Of the studies included in this review, 6 were performed in a neonatal intensive care unit, 47,48,50,52,55,56 1 was performed in intermediate/transition care nursery, 54 and 3 studies did not give a more detailed description of the nature of the hospital ward 49,51,53 . The studies included sick neonates 47,48,50–52,54–56 but excluded participants with critical illnesses.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the status of the neonates, 3 studies included healthy, full-term neonates 49,51,53 ; 1 study described sick, full-term neonates 55 ; 1 study involved sick, full-term neonates, and neonates in the mild preterm category (born 35 to 40+6 weeks of gestational age) 54 ; and 5 studies described preterm infants (born before 37 weeks of gestational age) 47,48,50,52,56 . Of the studies included in this review, 6 were performed in a neonatal intensive care unit, 47,48,50,52,55,56 1 was performed in intermediate/transition care nursery, 54 and 3 studies did not give a more detailed description of the nature of the hospital ward 49,51,53 . The studies included sick neonates 47,48,50–52,54–56 but excluded participants with critical illnesses.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Williams et al 52 measured pain outcomes using heart rate variability (HRV) and changes in HR, while Ranger et al 50 assessed pain based on the cerebral tissue saturation index (TSI), as measured by near infrared spectroscopy. An additional 5 studies reported pain outcomes according to changes in physiological indicators in addition to the results of validated pain assessment scales; more specifically, these studies assessed pain based on changes in HR 48,51,55,56 and oxygen saturation. 47,51,55,56 Behavioral indicators were used to measure pain outcomes in 2 studies, 51,53 which both used crying time as the outcome variable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations